Inhibitory Effects of Litsea cubeba Oil and Its Active Components on Aspergillus flavus - Shiqi Xia; Hong Lin; Peilin Zhu; Peiling Wang; Shengliang Liao; Shangxing Chen; Zongde Wang; Guorong Fan (Journal of Food Quality)
Aspergillus flavus (A. flavus) is a frequent harmful fungal pathogen. It can infect traditional Chinese medicine materials and release aflatoxin, to cause both economic and human health effects. By comparing the inhibitory potential of Litsea cubeba oil and its active components to A. flavus CGMCC 3.4408, citral was confirmed to be the main component that inhibits the growth of A. flavus CGMCC 3.4408, and the EC50 was 163.65 mg L−1. The inhibitory effect of citral on A. flavus CGMCC 3.4408 was studied for colony growth rate, mycelium biomass, aflatoxin production, and microstructure. Citral slowed down the growth rate of colonies and reduced mycelium biomass and toxin production. Moreover, citral altered the morphology of fungal spores and mycelium. In addition, citral also has the inhibitory effects on the isolates of A. flavus from moldy traditional Chinese medicinal materials. Thus, citral can be used as a potential agent to check the growth of A. flavus or related fungal strains.